The effect of slaughter age on the lamb characteristics of Merino, South African Mutton Merino and Dorper lambs - Van der Westhuizen, E. J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2010.